E-HEALTH LITERACY AMONG STUDENTS - Gazibara, Tatjana; Cakic, Jelena; Cakic, Milica; Zejnelagic, Redzeb; Popovic, Aleksandra; Grgurevic, Anita (Medical Research, 2022)
Introduction/Aim: There is a lack of data on eHealth literacy and potential differences in eHealth literacy among university students. The aim of this study was to evaluate potential differences in eHealth literacy between students of sports and medicine. Material and Methods: From April to October 2017, we conducted a cross-sectional study at the Faculty of Sports and Physical Education and the Faculty of Medicine, University of Belgrade, Serbia,. A total of 89 sports students and 301 medical students were included. The eHealth Literacy Scale (eHEALS) was applied to evaluate eHealth literacy. Results: Compared with sports students, medical students had higher median eHEALS score (27 vs. 30, respectively, P=0.008). Also, medical students were two times more confident than sports students in where to locate helpful online health resources and how to use online health information. We did not obtain a significant hierarchical linear regression model for factors contributing to better eHealth literacy among sports students. In medical students, we observed that being female, residing outside of the capital city before studying at the University, younger age at first Internet use, use of health-related websites and smartphone apps as well as less strong influence of online health-related information on decision making was associated with better self- perceived eHealth literacy. Conclusion: Medical students perceived their eHealth literacy skills as more confident compared to sports students. Factors influencing better eHealth literacy seem to depend on their fields of study